MODEL PERANGKAT PEMBELAJARAN MENULIS BERDASARKAN PENDEKATAN PROSES GENRE BAGI SISWA SMP - Syamsi, Kastam (LITERA, 2013)
This research and development study aims to produce models of teaching kits for writing based on the genre process approach for junior high school students. The procedure employed the R2D2 model, consisting of three main stages, i.e. (1) definition, (2) design and development, and (3) dissemination. The data consisted of qualitative and quantitative data. The qualitative data were analyzed using the domain analysis technique with critical and reflective principles, while the quantitative data were analyzed using t-test with SPSS 16.0 for Windows. The study produces five models, i.e.: (1) a syllabus model, (2) a lesson plan model, (3) a learning materials model, (4) an evaluation instrument model, and (5) a teacher guide model of the teaching of writing. Based on the data analysis, the five models of teaching kits for writing are effective to improve the students' writing ability.